Multiphase electrolyte for membrane-free single-liquid single-tank structure zinc-bromine flow battery

By using a multiphase mixed electrolyte in a membrane-free zinc bromine flow battery, combining components such as zinc bromide, zinc chloride and 1-butyl-2 methylpyridine bromide and functional additives, the electrolyte solution is solved. The problem of easy crystallization at low temperatures and bromine diffusion at high temperatures has achieved stable operation and efficient performance of the battery under a wide temperature environment.

CN119481190APending Publication Date: 2025-02-18SOUTH CHINA UNIV OF TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411568752.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The electrolyte is easy to crystallize in low temperature environments, which limits the application effect of the battery in wide temperature environments. In addition, the bromine diffusion problem of traditional electrolytes at high temperatures is serious, affecting the battery's performance and stability.

Method used

Using a heterogeneous mixed electrolyte, including zinc bromide, zinc chloride, 1-butyl-2 methylpyridine bromide and a variety of functional additives, such as direct polyepoxy naphthol propionate sulfonate potassium salt and nicotinic acid , optimize the composition and structure of the electrolyte to improve its stability in wide temperature environment and bromine complexing ability at high temperatures.

Benefits of technology

By optimizing the composition of the electrolyte, the problem of crystallization of the electrolyte at low temperatures is solved, and the complexing capacity of bromine at high temperatures is improved, the service life of the battery is extended, and its operating stability and overall operation in a wide temperature environment are improved. performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005119914010000061
    Figure BDA0005119914010000061
  • Figure BDA0005119914010000071
    Figure BDA0005119914010000071
  • Figure BDA0005119914010000081
    Figure BDA0005119914010000081
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemical energy storage, in particular to an electrolyte for a zinc-bromine flow battery with a membrane-free single-liquid single-tank structure. The electrolyte is a multiphase mixed solution, wherein a light phase component mainly comprises an aqueous solution of zinc bromide, zinc chloride and 1-butyl-2-methyl pyridine bromide; and the heavy phase component of the electrolyte is mainly a bromine complex of 1-butyl-2-methyl brominated pyridine. The invention has the following remarkable beneficial effects: firstly, the zinc-bromine flow battery can normally operate under a membrane-free single electrolyte storage tank structure, so that the battery framework is simplified, and the initial installation cost is reduced; and secondly, the problems of bromine cross diffusion, zinc dendrite and the like of the membrane-free structure zinc-bromine flow battery are effectively solved by a plurality of trace special additives, the battery is ensured to run well under the membrane-free structure, and the battery performance is ensured while the cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of zinc-bromine liquid flow batteries, in particular to application of a multi-phase mixed electrolyte in a zinc-bromine liquid flow battery with a membrane-free single-liquid single-tank structure. Background Art

[0002] With the continuous rise in energy demand and the growing demand for renewable energy storage, zinc-bromine flow batteries have attracted widespread attention as a large-scale energy storage technology with great potential. Zinc-bromine flow batteries have many advantages such as high energy density, long life and high safety. However, there are still some problems that need to be solved in this technology. Among them, the electrolyte is crucial as one of the key factors affecting battery performance. Traditional zinc-bromine flow battery electrolytes have problems such as bromine volatilization, zinc dendrite growth, low conductivity and poor stability of the electrode / electrolyte interface, which seriously restrict the performance and service life of the battery.

[0003] At present, zinc-bromine flow batteries are divided into two categories: membrane-based dual-liquid dual-tank dual-pump structure and membrane-free single-liquid single-tank single-pump structure. Compared with membrane-based structure, membrane-free single-liquid single-tank single-pump zinc-bromine flow batteries have many advantages. Its structure is simple, and the membrane-free design eliminates the complex and difficult-to-maintain diaphragm, making the overall structure simpler and easy to assemble and disassemble. The single-tank single-pump design reduces the amount of equipment and system complexity, and has significant advantages in space occupancy and equipment maintenance. The cost is low, because no diaphragm is required, the procurement cost is reduced, and the single-tank single-pump also reduces the equipment cost, and the cost advantage is prominent in large-scale energy storage applications. The energy density is high, the electrolyte can be effectively utilized, the space and energy loss are reduced, and more energy can be stored under the same volume or mass.

[0004] Similarly, since there is no diaphragm to separate the positive and negative electrodes in the membrane-less structure battery, there are special requirements for the electrolyte performance indicators of this type of battery. BZ Magnes et al. elaborated on the application of 1-n-butyl-2-methyl-pyridinium bromide in the membrane-less zinc-bromine flow battery structure in patents CN104350641B and CN107534177B. The membrane-less zinc-bromine flow battery electrolyte using 1-butyl-2-methylpyridinium bromide as a bromine complexing agent has the characteristics of low concentration of free elemental bromine in the aqueous phase and good stability at about 55°C, which is very suitable for membrane-less zinc-bromine flow batteries. However, when the ambient temperature is lower than 25°C, the concentration of 1-butyl-2-methylpyridinium bromide in the electrolyte is usually in the range of 0.8 to 1.5 mol / L, which will cause the electrolyte to crystallize, thereby hindering the normal operation of the battery. Although it can better guarantee the operation of the device at a temperature above 30°C, the crystallization problem still exists. This crystallization phenomenon, to a certain extent, limits the application effect of this type of electrolyte in low-temperature environments, and also brings challenges to the practical application of membraneless zinc-bromine flow batteries. Further research and solutions are needed to expand its applicable temperature range and improve the overall performance and stability of the battery.

[0005] In view of the special requirements of the membraneless zinc-bromine flow battery structure, ordinary zinc-bromine flow battery electrolytes can no longer guarantee the normal operation and operation of the membraneless zinc-bromine flow battery. Therefore, in order to fully demonstrate the advantages of membraneless zinc-bromine flow batteries compared to other types of batteries, it is extremely critical to develop an electrolyte that matches the structural characteristics of membraneless zinc-bromine flow batteries. Through the development of such electrolytes, not only can the unique operating requirements of membraneless batteries be met, but also the development and application of related technologies can be further promoted, and the technical level in this field can be improved, laying a solid foundation for the application of membraneless zinc-bromine flow batteries in a wider range of fields, so that they can play a greater role in energy storage and other aspects. Summary of the invention

[0006] The present invention focuses on exploring how to broaden the temperature range of membraneless zinc-bromine flow battery electrolyte, improve the high temperature stability of the electrolyte, and reduce the bromine diffusion problem. To this end, a variety of functional additives are proposed in the membraneless zinc-bromine flow battery electrolyte. These functional additives can make the electrolyte stable in a wide temperature range, thereby ensuring the long-term stable operation of the battery under a wide temperature environment; improve the complexing ability of bromine at high temperature, reduce the self-discharge of the battery, thereby improving the overall performance of the battery, and providing strong technical support and guarantee for the efficient operation and wide application of membraneless zinc-bromine flow batteries.

[0007] In order to achieve the above purpose, the following technical solutions are adopted:

[0008] A multiphase mixed electrolyte for a membraneless single-liquid single-tank structure zinc-bromine flow battery, comprising the following components:

[0009] The active material in the electrolyte is zinc bromide, and the preferred active material concentration is 1.8-3 mol / L, and the more preferred zinc bromide concentration is 2-2.5 mol / L.

[0010] The supporting electrolyte in the electrolyte is selected from one of zinc chloride and ammonium chloride, and the preferred supporting electrolyte concentration is 0.1-0.8 mol / L; more preferably, zinc chloride is used as the supporting electrolyte, and the zinc chloride concentration is 0.2-0.4 mol / L.

[0011] The bromine complexing agent in the electrolyte is 1-butyl-2-methylpyridinium bromide, and the preferred concentration of 1-butyl-2-methylpyridinium bromide is 0.5-1.2 mol / L; the more preferred concentration is 0.8-1.2 mol / L.

[0012] The preferred amount of bromine added to the electrolyte is between 1.0 and 10.0% w / v, and the more preferred amount of bromine added is between 3.0 and 5.0% w / v.

[0013] In order to optimize the solubility characteristics of 1-butyl-2-methylpyridinium bromide in an environment below 28°C, avoid the occurrence of crystallization of the electrolyte, and promote and regulate the nucleation process of the zinc anode during battery charging, inhibit the formation and growth rate of zinc dendrites; adjust the distribution ratio of the bromine complexing agent between the water phase and the oil phase, and regulate the viscosity of the electrolyte, etc., to ensure that the electrolyte operates stably in a membrane-free zinc-bromine flow battery, the present application also adds a variety of functional additives, the specific components are as follows:

[0014] The electrolyte is added with linear polyepoxy naphthol propanesulfonic acid potassium salt and nicotinic acid, wherein the preferred addition amount of linear polyepoxy naphthol propanesulfonic acid potassium salt is 0.1-0.8% w / v, and the added amount of nicotinic acid is 0.01-0.1% w / v; the more preferred addition amount of linear polyepoxy naphthol propanesulfonic acid potassium salt is 0.3-0.5% w / v, and the added amount of nicotinic acid is 0.03-0.08% w / v.

[0015] Sodium benzoate, lead bromide and vanadyl sulfate are also added to the electrolyte. Preferably, the amount of sodium benzoate added is 0.05-0.2% w / v, the amount of lead bromide added is 0.01-0.1% w / v, and the amount of vanadyl sulfate added is 0.01-0.05% w / v; more preferably, the amount of sodium benzoate added is 0.08-0.12% w / v, the amount of lead bromide added is 0.01-0.03% w / v, and the amount of vanadyl sulfate added is 0.01-0.015% w / v.

[0016] A chelating accelerator is added to the electrolyte, and the amount of the chelating accelerator added is 0.1-0.8% w / v; a more preferred amount of the chelating accelerator added is 0.1-0.15% w / v.

[0017] A viscosity modifier is added to the electrolyte, and the amount of the viscosity modifier added is 0.5-1.5% w / v of the additive; a more preferred amount of the viscosity modifier added is 0.8-1.2% w / v.

[0018] The present invention not only gives full play to the advantages of 1-butyl-2-methylpyridinium bromide in the electrolyte of the membrane-free zinc-bromine flow battery through the synergistic effect of special additives in the electrolyte, but also solves the defect that the electrolyte is easy to crystallize at room temperature after the complexing agent is used in the electrolyte, thereby improving the performance of the electrolyte and the overall stability of the battery, and providing a strong guarantee for the efficient operation of the membrane-free zinc-bromine flow battery.

[0019] The present invention has the following significant beneficial effects:

[0020] First, it enables zinc-bromine flow batteries to operate normally in a membrane-free single electrolyte storage tank structure, thereby simplifying the structure of zinc-bromine flow batteries and reducing initial installation costs. Through innovative technical means and ingenious design, the battery system has been freed from the shackles of traditional complex structures, making the equipment composition more concise and achieving significant results in cost control, providing strong support for its large-scale promotion and application, and enhancing the competitiveness and application potential of zinc-bromine flow batteries in the market.

[0021] Secondly, trace amounts of a variety of special additives have effectively solved the problems faced by membraneless zinc-bromine flow batteries, such as easy crystallization of electrolyte at room temperature, bromine cross-diffusion, and zinc dendrites, effectively ensuring the normal operation of membraneless batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the type I membrane-free zinc-bromine flow battery used in the experiment in Example 1. Figure 1 a is a schematic diagram of the structure of a type I battery, 1b is a schematic diagram of the positive and negative electrodes of a type I battery, 1c is a schematic diagram of the appearance of a type I battery, and 1d is a schematic diagram of the operation of a type I battery.

[0023] Figure 2 This is a type II zinc-bromine flow battery without a membrane structure used in the experiments of Example 2 and Example 3. Figure 2 a is a schematic diagram of the structure of a type II battery, 2b is a schematic diagram of the positive and negative electrodes of a type II battery, 2c is a schematic diagram of the appearance of a type II battery, and 2d is a schematic diagram of the operation of a type II battery.

[0024] Figure 3 This is the appearance of zinc dendrites on the negative electrode surface of the type I membraneless zinc-bromine flow battery in Example 1 after a 24-hour charge and discharge experiment.

[0025] Figure 4 This is the appearance of zinc dendrites on the negative electrode surface of the type II membraneless zinc-bromine flow battery in Example 2 after a 24-hour charge and discharge experiment.

[0026] Figure 5 This is the appearance of zinc dendrites on the negative electrode surface of the type II membraneless zinc-bromine flow battery in Example 3 after a 24-hour charge and discharge experiment. DETAILED DESCRIPTION

[0027] The present application is further described in detail below in conjunction with embodiments, but the present application is not limited to these embodiments.

[0028] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0029] The free elemental bromine concentration in the aqueous phase of the electrolyte was compared and tested by UV spectrophotometry. The viscosity was measured using a 1833 Pinnacle viscometer. The conductivity of the sample electrolyte was measured using an INESA conductivity meter.

[0030] The battery performance test uses Hubei Lanbo BT-2018B charging and discharging instrument. The electroplating test uses a 267ml Hull cell, and the electroplating power source is Hubei Lanbo BT-2018B charging and discharging instrument. The CV test uses Chenhua electrochemical workstation CHI 760E.

[0031] The experimental type I and type II membraneless zinc-bromine flow batteries were designed by ourselves and assembled after 3D printing and CNC machining of accessories. The battery components of both structures are composed of an upper end plate (with flow channel), a negative plate, a PEFE guide frame, a positive plate, a bottom lower end plate (with flow channel) and corresponding silicone sealing gaskets. Among them, the positive plate of the type I structure is a composite of an MMO-coated titanium mesh and a titanium substrate, and the negative plate is made of pure titanium; the positive and negative electrodes of the type II structure are both CNC-machined porous carbon plates. The electrolyte is pumped into the battery through the lower end plate, flows horizontally through the reaction areas of the positive and negative plates of the battery, and then flows back to the electrolyte storage tank through the lower end plate. For details, see Figure 1 and Figure 2 .

[0032] Embodiment 1:

[0033] A multiphase electrolyte for a membraneless single-liquid single-tank structure zinc-bromine flow battery: composed of 2.24 mol / L zinc bromide, 0.26 mol / L zinc chloride, 1.0 mol / L 1-butyl-2-methylpyridinium bromide, 4% w / v elemental bromine, 0.3% w / v straight polyepoxynaphtholpropanesulfonic acid potassium salt, 0.06% w / v nicotinic acid, 0.12% w / v sodium benzoate, 0.01% w / v lead bromide, 0.01% w / v vanadyl sulfate, 0.128% w / v chelating promoter, and 1% w / v viscosity regulator.

[0034] The electrolyte is prepared with deionized water at room temperature. First, the vapor pressure above the electrolyte is tested. The vapor pressure above the electrolyte under the room temperature condition is tested by the steady-state method using a vapor pressure meter. The saturated vapor pressure of 100% SOC is 0.009 kPa, and the complexing ability of the electrolyte surface for bromine meets the working requirements of the electrolyte. The electrolyte sample is directly placed in a refrigerator at a constant temperature of -5°C. After standing for 24 hours, the experimental sample is observed to be in a solution state. No crystalline crystals appear in the experimental sample. The low-temperature performance of the electrolyte meets the requirements.

[0035] Under the conditions of electrolyte temperature of room temperature, 35°C and 55°C, and three states of charge (SOC%) of 0, 50% and 100%, the free elemental Br2 concentration in the aqueous phase of the electrolyte, the viscosity of the aqueous phase and the conductivity were measured according to the above-mentioned method, as shown in Table 1. The data show that in the temperature range from room temperature to 55°C, and the state of charge of 0 to 100% SOC, the free bromine concentration in the aqueous phase of the sample electrolyte is maintained in the range of 0.0020 to 0.0052 mol / L (~%), which can better meet the working requirements of membraneless ZBFB and show good stability of complexed bromine in a wide temperature range.

[0036] This embodiment uses a type I ZBFB experimental battery to conduct a 24-hour charge and discharge experiment on the electrolyte, and the charge and discharge operation of this battery is normal. After measurement and calculation, the average voltage efficiency of the battery is 64.5%, and the average coulomb efficiency is 68.3%. In the future, the voltage efficiency and coulomb efficiency can be further improved by optimizing the battery structure design, enhancing the performance of the positive and negative electrode materials, and adjusting the battery operating parameters. After the experiment, the negative electrode of the battery is relatively flat, and the condition of the zinc dendrites is as follows. Figure 3 shown.

[0037] Table 1 Performance test of membraneless ZBFB electrolyte of Example 1

[0038]

[0039] Embodiment 2:

[0040] A multiphase electrolyte for a membraneless single-liquid single-tank structure zinc-bromine flow battery: composed of 2.40 mol / L zinc bromide, 0.40 mol / L zinc chloride, 1.20 mol / L 1-butyl-2-methylpyridinium bromide, 5% w / v bromine element, 0.4% w / v straight polyepoxy naphthol propanesulfonic acid potassium salt, 0.06% w / v nicotinic acid, 0.12% w / v sodium benzoate, 0.03% w / v lead bromide, 0.01% w / v vanadyl sulfate, 0.15% w / v chelating promoter, and 1.2% w / v viscosity regulator.

[0041] The electrolyte was prepared with deionized water at room temperature. The performance index of the electrolyte was measured according to the above method. The data showed that the electrolyte met the stamping requirements of the zinc-bromine flow battery without membrane structure well, as shown in Table 2.

[0042] In this embodiment, a type II ZBFB experimental battery was used to carry out a 24-hour charge and discharge experiment on the electrolyte, and the charge and discharge operation of this battery was normal. After testing, the average voltage efficiency of the battery was 66.8%, and the average coulomb efficiency was 70.5%. Similarly, the voltage efficiency and coulomb efficiency can be further improved by optimizing the battery structure design, enhancing the performance of the positive and negative electrode materials, and regulating the battery operating parameters. After the experiment, the negative electrode of the battery was relatively flat, and the zinc dendrites were as follows. Figure 4 shown.

[0043] Table 2 Performance test of membraneless ZBFB electrolyte of Example 2

[0044]

[0045]

[0046] Embodiment 3:

[0047] A multiphase electrolyte for a membraneless single-liquid single-tank structure zinc-bromine flow battery: composed of 2.0 mol / L zinc bromide, 0.24 mol / L zinc chloride, 0.80 mol / L 1-butyl-2-methylpyridinium bromide, 3% w / v bromine element, 0.3% w / v straight polyepoxynaphtholpropanesulfonic acid potassium salt, 0.05% w / v nicotinic acid, 0.08% w / v sodium benzoate, 0.015% w / v, vanadyl sulfate (0.015% w / v), 0.10% w / v chelating promoter, and 0.8% w / v viscosity regulator.

[0048] The electrolyte was prepared with deionized water at room temperature. The performance index of the electrolyte was measured according to the above method. The data showed that the electrolyte met the stamping requirements of the zinc-bromine flow battery without membrane structure well, as shown in Table 3.

[0049] The II-type ZBFB experimental battery was used to conduct a 24-hour charge and discharge experiment of the electrolyte. The battery charge and discharge operation was normal. The average battery voltage coulomb efficiency was 67.5%, and the average battery coulomb efficiency was 72.8%. After the experiment, the negative electrode of the battery was relatively flat, and the zinc dendrites were as follows: Figure 5 shown.

[0050] Table 3 Performance test of membraneless ZBFB electrolyte of Example 2

[0051]

[0052]

[0053] The above are only a few embodiments of the present application and do not constitute any form of limitation on the present application. The embodiments disclosed in the present application are not intended to limit the present application. Any technical personnel familiar with the profession who make slight changes using the above technical contents without departing from the scope of the technical solution of the present application are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A multiphase electrolyte for a membraneless single-liquid single-tank structure zinc-bromine flow battery, characterized in that: The electrolyte contains: active material, supporting electrolyte, bromine complexing agent and bromine element.

2. The multiphase electrolyte for a membraneless single-liquid single-tank structure zinc-bromine flow battery according to claim 1, characterized in that: The active substance in the electrolyte is zinc bromide with a concentration of 1.8 to 3.0 mol / L.

3. The multiphase electrolyte for a membraneless single-liquid single-tank structure zinc-bromine flow battery according to claim 1, characterized in that: The supporting electrolyte in the electrolyte is selected from one of zinc chloride and ammonium chloride, and the concentration of the supporting electrolyte is 0.1-0.8 mol / L.

4. The multiphase electrolyte for a membraneless single-liquid single-tank structure zinc-bromine flow battery according to claim 1, characterized in that: The bromine complexing agent is 1-butyl-2-methylpyridinium bromide, and the concentration is 0.5-1.2 mol / L.

5. The multiphase electrolyte for a membraneless single-liquid single-tank structure zinc-bromine flow battery according to claim 1, characterized in that: The added amount of the bromine element is 1.0 to 10.0% w / v.

6. A multiphase electrolyte for a membraneless single-liquid single-tank structure zinc-bromine flow battery according to any one of claims 1 to 5, characterized in that: The electrolyte is further added with linear polyepoxy naphthol propanesulfonic acid potassium salt and nicotinic acid, wherein the amount of linear polyepoxy naphthol propanesulfonic acid potassium salt added is 0.1-0.8% w / v; The amount of niacin added is 0.01 to 0.1% w / v.

7. A multiphase electrolyte for a membraneless single-liquid single-tank structure zinc-bromine flow battery according to any one of claims 1 to 5, characterized in that: Sodium benzoate, lead bromide and vanadyl sulfate are also added to the electrolyte, the amount of sodium benzoate added is 0.05-0.2% w / v, the amount of lead bromide added is 0.01-0.1% w / v, and the amount of vanadyl sulfate added is 0.01-0.05% w / v.

8. A multiphase electrolyte for a membraneless single-liquid single-tank structure zinc-bromine flow battery according to any one of claims 1 to 5, characterized in that: A chelating accelerator is also added to the electrolyte, and the amount of the chelating accelerator added is 0.1-0.8% w / v.

9. A multiphase electrolyte for a membraneless single-liquid single-tank structure zinc-bromine flow battery according to any one of claims 1 to 5, characterized in that: A viscosity modifier is also added to the electrolyte, and the amount of the viscosity modifier added is 0.5-1.5% w / v.

Citation Information

Patent Citations

  • Additives for zinc-bromine membrane-free flow batteries

    CN104350641B

  • Additives for flow batteries

    CN107534177B